2016
DOI: 10.1111/gbb.12354
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA methyltransferases regulates cocaine self‐administration by rats: a genome‐wide DNA methylation study

Abstract: DNA methylation is a major epigenetic process which regulates the accessibility of genes to the transcriptional machinery. In the present study, we investigated whether modifying the global DNA methylation pattern in the brain would alter cocaine intake by rats, using the cocaine self-administration test. The data indicate that treatment of rats with the DNA methyltransferase inhibitors 5-aza-2'-deoxycytidine (dAZA) and zebularine enhanced the reinforcing properties of cocaine. To obtain some insights about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 56 publications
3
27
0
Order By: Relevance
“…5-Aza-dc is well known to be cytotoxic and its toxicity depends on the dosage and exposure time [26]. Relevant research has shown that in the concentration range of 0.1ug/ulto 2ug /ul in specific brain region [22, 23, 27, 28], 5-Aza-dc did not interfere with the locomotor activities of rats, in line with our OFT results. In addition, our results suggest that 5-Aza-dc (1μg /0.5μl/side) in the mPFC do not affect the total fluid intake (Fig 4E) or body weight (S1 Fig) of rats.…”
Section: Discussionsupporting
confidence: 90%
“…5-Aza-dc is well known to be cytotoxic and its toxicity depends on the dosage and exposure time [26]. Relevant research has shown that in the concentration range of 0.1ug/ulto 2ug /ul in specific brain region [22, 23, 27, 28], 5-Aza-dc did not interfere with the locomotor activities of rats, in line with our OFT results. In addition, our results suggest that 5-Aza-dc (1μg /0.5μl/side) in the mPFC do not affect the total fluid intake (Fig 4E) or body weight (S1 Fig) of rats.…”
Section: Discussionsupporting
confidence: 90%
“…Using an antibody pulldown specific to 5hmC (hMeDip-seq), this group identified over 10,000 peaks of differential hydroxymethylation in the mouse NAc. As was the case with methylome studies [53,68], the majority of cocaine-induced changes in 5hmC occurred in gene bodies and intergenic regions. Combining this dataset with chromatin state information revealed that 5hmC changes were enriched at enhancer sites and regions that frequently switched chromatin states in the cocaine or control groups [47].…”
Section: Cocaine-associated Dysregulation Of Methylation Dynamicsmentioning
confidence: 77%
“…In a second PFC study, Fonteneau and colleagues [68] trained rats to self-administer cocaine, either alone or after intra-ventricular injections of DNMT inhibitors. As was seen in mice, self-administration resulted in numerous DMRs, most of which fell within gene bodies and intergenic regions.…”
Section: Cocaine-associated Dysregulation Of Methylation Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbances in epigenetics, particularly DNA methylation, have been implicated in the pathophysiology of several psychiatric disorders, such as eating disorders (11), depression (12), schizophrenia (13), cocaine addiction (14), and alcohol dependence (15). Epigenetic research on MA addiction is at a relatively early stage, far behind that of cancer or other complex disorders, and far behind that of cocaine, heroin, and other substance abuse.…”
Section: Introductionmentioning
confidence: 99%